(untitled) (Docentes 2.0 Journal, 2026)
The concept of digital citizenship is fundamental in today’s technological age and is defined as the set of skills, attitudes, and practices that enable individuals to participate ethically, critically, safely, and responsibly in contemporary digital environments. The objective of this research was to identify the main challenges and limitations of digital citizenship in Latin America during the period 2021–2025. The methodology employed was a systematic review, following the PRISMA 2020 protocol. The research was framed within the pragmatic paradigm, using a systematic method, a mixed-methods approach, a narrative-thematic design, and a cross-sectional, bibliographic-analytical, documentary type. Systematic searches were conducted in the academic databases Scopus, ScienceDirect, SciELO, ScienceOpen, Wiley, and Redalyc using specifically defined keywords. Thirty-four articles were carefully selected from an initial 179 manuscripts after applying rigorous inclusion and exclusion criteria. The main findings identified eight categories of challenges and seven of limitations, highlighting in particular the digital divide, deficient digital skills, emerging ethical challenges, the exclusion of vulnerable groups, critical gaps in technological infrastructure, unequal internet access, and persistent socioeconomic inequality. The findings reveal that the digital divide constitutes the most significant and structural obstacle, underscoring the urgent need to implement comprehensive, sustainable public policies that effectively reduce technological inequalities and guarantee a truly inclusive and responsible digital citizenship across the Latin American region.